Development and Validation of a Situational Judgment Test of Emotional Intelligence. (7th February 2013) - Sharma, Sudeep; Gangopadhyay, Mugdha; Austin, Elizabeth; Mandal, Manas K.
<x xml:space="preserve">Abstract</x> The present study describes the development and validation of a situational judgment test (SJT) of emotional intelligence (EI). Initially, 80 situations and three response alternatives for each situation were created based on the available theoretical models. Principal component factor analysis with direct oblimin rotation of data (N = 213) yielded a three‐factor structure with 46 items. These factors were (1) utilizing own emotion, (2) sensing other's emotion, and (3) understanding emotional context. Additional studies showed that the measure had good internal consistency and test‐retest reliability. None of the three factors strongly correlated with the Big Five factors of personality (NEO Five‐Factor Inventory, thus establishing its identity as a construct distinct from personality. Findings of confirmatory factor analysis on secondary data reconfirm the three‐factor model for a 46‐item SJT of EI. The second study also found no correlation among these three factors, intelligence scores measured using Raven's Matrices, and trait EI score measured using the Trait Emotional Intelligence Questionnaire. The third study was conducted in order to determine the relationship of SJT of EI with academic achievement and life satisfaction. All three factors of SJT‐based EI measure were significantly associated with academic achievement and life satisfaction.